A study of "up" - "down" in English and "lên" - "xuống" in Vietnamese : a cognitive semantics perspective - Võ, Thị Cẩm Thùy. (The University of Da Nang, 2011)
Introduction; Literature review and theoretical background; Methods and procedures...